Evaluation of D‐ribose pharmacokinetics, dose proportionality, food effect, and pharmacodynamics after oral solution administration in healthy male and female subjects. (16th December 2013) - Thompson, Jeff; Neutel, Joel; Homer, Ken; Tempero, Ken; Shah, Ajit; Khankari, Raj
Abstract This was a double blind, randomized, crossover study of three periods evaluating pharmacokinetics and pharmacodynamics in 12 healthy, adult subjects after administration of D‐ribose powder for oral solution, 2.5, 5.0, and 10.0 g, under fasting conditions followed by an open label, randomized, fourth period assessing the effect of food on the pharmacokinetics of D‐ ribose (10.0 g) under fed conditions with either a high fat (HF, N = 6) or high carbohydrate (HC, N = 6) meal. D‐ribose was absorbed rapidly with mean Tmax ranging between 18 and 30 minutes. Cmax and AUC increased more than proportionally with dose indicating increased absorption and saturation of metabolism. When D‐ribose was administered with meals, Tmax was unchanged; however, Cmax and AUC decreased by 42.6% and 40.8%, respectively with HF and 69.1% and 64.9%, respectively with HC. The amount of D‐ribose in urine ranged from 4.15% to 7.20% of the administered dose. Dose‐related decreases in serum glucose up to 26.3 mg/dL (30.3% of baseline) occurred in the first 60 minutes post dose and insulin response attained a dose‐related peak 15 minutes post dose. D‐ribose was generally safe and well tolerated in the dose range studied.